“But how then shall I imitate thee, and/ Copie thy fair, though bloudie hand?”(“The Thanksgiving”, vv.15-16) - Guillaume Coatalen (Sillages Critiques)
Herbert first imitates God’s Word. His Temple is deliberately built almost exclusively on the Bible, which it quotes or glosses extensively. Second, the work belongs to the rich tradition of the imitation of Christ, which was still popular in the early modern age. Thus, as a topic, imitation does not simply belong to poetics, but more significantly to theology, and more precisely to salvation. Herbert’s use of the term and Donne’s exegesis should allow us to understand better how the poet solves the central paradox of imitation in his work: is it possible to imitate the infinite? If the poet is God’s secretary, how can Christ imitate himself in his verse? To imitate is largely based on repetition, whether the poet repeats himself or echoes the Scriptures. It plays a crucial part in recreating the miracle of redemption in the poem. Lastly, exegesis, which Herbert practices in a significant number of poems, depends on imitating.